The impact of strategic intelligence on crisis management in light of the spread of the Corona pandemic by applying it to the Saudi banking sector in the Asir region - Al-Asmari, Abdurrahman Ali Farraj (Journal of Economic, Administrative and Legal Sciences, 2022)
There is no doubt that the Corona pandemic that struck the world had direct and indirect effects on all areas of our life. Finance and economy, represented in the banking sector, was no exception to this. To know the effects, this study aimed specifically at studying the impact of strategic intelligence on the management of crises in the banking sector in the Kingdom of Saudi Arabia, specifically in the Asir region (the cities of Abha and Khamis Mushait), and knowing the extent to which the employees of those banks are aware of the concept of strategic intelligence in achieving crisis management. The descriptive correlative approach was applied after designing a questionnaire that includes three sections, including the personal data section, the strategic intelligence section, and the crisis management section, and it was distributed to 154 samples, They were randomly selected from over 2000 employees in the area. As a result of the field survey, it showed that some indicators and dimensions were applied at high rates, such as foresight, vision, thinking, motivation, partnership, and the crisis management perspicacity, in addition to the availability of a high application of strategic intelligence. This study recommended the need to develop future forward-looking plans to reach a better distinction in the face of future crises, with the relentless pursuit by the management of banks to reach a better mental image of customers and to follow partnership in achieving a higher and more comprehensive development by collecting the elements of that image and then placing it under the brainstorming mechanism to be Analysis and detection of internal factors within a high capacity.